Learning and instruction : a SERP research agenda - Donovan, Suzanne; Pellegrino, James W. (National Academies Press, 2004)
"The Strategic Education Research Partnership (SERP) is a bold, ambitious plan that proposes a revolutionary program of education research and development. Its purpose is to construct a powerful knowledge base, derived from both research and practice, that will support the efforts of teachers, school administrators, colleges of education, and policy officials - with the ultimate goal of significantly improving student learning." "With a vision of multiple networks through which focused, coordinated, and sustained programs of research and development would be carried out - often in schools or school districts that serve as field sites - the National Research Council proposed an organizational design that would implement the essential mission of SERP. The essence of that plan was captured in Strategic Education Research Partnership. Following up with specifics on one of the networks proposed in that earlier book, Learning and Instruction details the kind of research and development that would make a genuine difference to teaching and learning in three subject areas - reading, mathematics, and science." "The proposals in this book have the potential to substantially improve the knowledge base that supports teaching and learning by pursuing answers to questions at the core of teaching practice. It calls for the linking of research and development including instructional programs, assessment tools, teacher education programs and materials. Best of all, the book provides a solid framework for a program of research and development that will be genuinely useful to classroom teachers."--Jacket